Low-cost colorimetric setup for concentration measurement of manganese ions based on optical absorbance - Maidan Dali, Mohd Rumaizan; Ali, Nurul Hidayah; Mohamad Robi, Fatin Izyani; Osman, Mohamed Syazwan; Abd Rahman, Mohamad Faizal (Institute of Advanced Engineering and Science, 2023)
This study presents a cost-effective setup for measuring the concentration of Mn2+ ions using colorimetry. The current method involves a calibration curve created with expensive and large commercial laboratory-based instruments, limiting its use in financially constrained situations. To address this issue, the study proposes a low-cost setup consisting of a light-emitting diode and photodiode that utilizes colorimetric and absorbance effects for Mn2+ concentration measurement. Mn2+ colorimetric samples were prepared using the 1-(2-pyridylazo)-2-naphthol (PAN) method with concentrations ranging from 0.2 to 1.0 mg/L. The samples were tested using the proposed setup, followed by a spectrophotometry test to determine the optimal configuration for the setup. The validity of the setup was confirmed by measuring the voltage and calculating the optical absorbance, which exhibited a good correlation with the concentration, consistent with the initial expectation. The correlation coefficient for voltage and absorbance against Mn2+ concentration was found to be 0.9976 and 0.9987, respectively, indicating good linearity and suitability as a calibration curve for Mn2+ detection and measurement. Consequently, the study’s objectives were successfully achieved, and the proposed setup is considered a viable platform for more complex applications, such as real-time monitoring activities.